Pengaruh Kontribusi Pajak Daerah dan Retribusi Daerah Terhadap Belanja Daerah pada Kabupaten atau Kota di Provinsi Jawa Barat - Neisya Amaliah; Yuliana Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The primary goal of this research is to determine the effect of local tax and retribution percentages on regional spending in West Java Province's districts and cities. The data in this research was analysed quantitatively using Eviews 12 software and multiple linear regression. This research used nine cities and eighteen districts in West Java Province as its population. A total of 135 samples were included in this investigation, using a saturation sampling strategy. This data is derived from secondary sources, namely audit reports on financial accounts from local governments. These reports, which span the fiscal years 2018–2022, are available on the Republic of Indonesia's Supreme Audit Agency's website. The reports provide data on the amount of money that was actually spent. At least in part, this study's results demonstrate that local taxes significantly affect spending at the municipal level. Quite a bit of weight is borne by local punishment on local spending. Municipal levies and taxes have a significant combined effect on district and city budgets in West Java Province.